The Regulation of Adipose Tissue Health by Estrogens - Steiner, Benjamin M.; Berry, Daniel C. (Frontiers in Endocrinology, 2022)
Obesity and its’ associated metabolic diseases such as type 2 diabetes and cardiometabolic disorders are significant health problems confronting many countries. A major driver for developing obesity and metabolic dysfunction is the uncontrolled expansion of white adipose tissue (WAT). Specifically, the pathophysiological expansion of visceral WAT is often associated with metabolic dysfunction due to changes in adipokine secretion profiles, reduced vascularization, increased fibrosis, and enrichment of pro-inflammatory immune cells. A critical determinate of body fat distribution and WAT health is the sex steroid estrogen. The bioavailability of estrogen appears to favor metabolically healthy subcutaneous fat over visceral fat growth while protecting against changes in metabolic dysfunction. Our review will focus on the role of estrogen on body fat partitioning, WAT homeostasis, adipogenesis, adipocyte progenitor cell (APC) function, and thermogenesis to control WAT health and systemic metabolism.